2018
DOI: 10.1016/j.neuroimage.2018.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Mutual connectivity analysis of resting-state functional MRI data with local models

Abstract: Functional connectivity analysis of functional MRI (fMRI) can represent brain networks and reveal insights into interactions amongst different brain regions. However, most connectivity analysis approaches adopted in practice are linear and non-directional. In this paper, we demonstrate the advantage of a data-driven, directed connectivity analysis approach called Mutual Connectivity Analysis using Local Models (MCA-LM) that approximates connectivity by modeling nonlinear dependencies of signal interaction, ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 74 publications
(141 reference statements)
0
8
0
1
Order By: Relevance
“…Dynamic time warping has been demonstrated to capture the non-stationarity in simulated functional MRI data 26,27 . The importance of non-linear and directional dependencies among BOLD signals is highlighted by means of mutual connectivity 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic time warping has been demonstrated to capture the non-stationarity in simulated functional MRI data 26,27 . The importance of non-linear and directional dependencies among BOLD signals is highlighted by means of mutual connectivity 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Though CCM does not concern itself with the dimension of the attractor (d), it relates to the embedding dimension of the reconstructed manifold (E) through the Whitney embedding theorem (E ≤ 2d + 1). DSouza et al (2018) showed the deleterious effect that a high repetition time (TR) has on attractor reconstruction. Following the example of McFarlin et al (2013) who reported improvements in connectivity analysis 1 Convergence is a key property for inferring causality, it is limited by observational error, process noise, and time series length.…”
Section: Data Preparationmentioning
confidence: 99%
“…该方法可以表述为 [47] S = argmintr( ) log + , 式如下: [54] . 因其所需数据量较少, 并且能够有效地反 映非线性特征等特点, 非常适合用于基于功能核磁共 振数据进行脑区间功能连接的分析 [55,56] . 通过收敛交叉映射方法构建脑功能连接网络的流 程如图2所示.…”
Section: 如上所述 Dmn内部激活模式及功能连接的异常往往unclassified